2016
DOI: 10.1002/2015ja021691
|View full text |Cite
|
Sign up to set email alerts
|

Dipolarizing flux bundles in the cis‐geosynchronous magnetosphere: Relationship between electric fields and energetic particle injections

Abstract: Dipolarizing flux bundles (DFBs) are small flux tubes (typically <3 RE in XGSM and YGSM) in the nightside magnetosphere that have magnetic field more dipolar than the background. Although DFBs are known to accelerate particles, creating energetic particle injections outside geosynchronous orbit (trans‐GEO), the nature of the acceleration mechanism and the importance of DFBs in generating injections inside geosynchronous orbit (cis‐GEO) are unclear. Our statistical study of cis‐GEO DFBs using data from the Van … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 71 publications
8
95
4
Order By: Relevance
“…Figure d shows magnetic field fluctuations during this event, in Geocentric solar magnetospheric (GSM) coordinates. Bz is strongly enhanced at the injection front, indicating a dipolarization of the magnetic field (Liu et al, ). Figures e and f show spectrograms of electric and magnetic field wave power, respectively.…”
Section: Observationsmentioning
confidence: 99%
“…Figure d shows magnetic field fluctuations during this event, in Geocentric solar magnetospheric (GSM) coordinates. Bz is strongly enhanced at the injection front, indicating a dipolarization of the magnetic field (Liu et al, ). Figures e and f show spectrograms of electric and magnetic field wave power, respectively.…”
Section: Observationsmentioning
confidence: 99%
“…They then propagate earthward as an integral part of bursty bulk flows (BBFs) (Angelopoulos et al, ; Liu et al, ) over more than 10 R E for a few minutes (Birn et al, ; Runov et al, ) before eventually stopping near the inner edge of the plasma sheet (e.g., Dubyagin et al, ; Ohtani, Singer, & Mukai, ). Some (~1/3) of them may penetrate deep into the inner magnetosphere (within the GEO) (Liu et al, ). The leading edge of a DFB is characterized by a sharp enhancement of B z (in GSM, the default coordinate system of this paper unless otherwise specified) known as a dipolarization front (DF) (Nakamura, Matsumoto, & Fujimoto, ) or a reconnection front (Angelopoulos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This acceleration can be either adiabatic (Ashour‐Abdalla et al, ; Deng et al, ; Fu et al, ; Runov et al, ), most simply understood as caused by the electric field accompanying moving DFBs (e.g., Artemyev et al, ; Gabrielse et al, ; Zhou et al, ), or nonadiabatic due to large amplitude waves observed in the DFB vicinity (Zhou et al, ). For some DFBs that can penetrate into the inner magnetosphere, the electric field related to the DFB evolution can still be large and lead to significant local particle acceleration (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar acceleration deep inside geosynchronous orbit may require even larger electric fields. According to a recent statistical study [Liu et al, 2016], the electric fields associated with mesoscale injections inside geosynchronous can be as large as ≳10 mV/m, but on average do not exceed 6 mV/m.…”
Section: 1002/2016ja023304mentioning
confidence: 99%
“…Gkioulidou et al [2015] reported a dispersionless ion injections at as low as L = 5.5 associated with a sharp dipolarization of magnetic field, similar to dipolarization fronts in the magnetotail. A statistical analysis of dipolarization fronts measured at Van Allen Probes [Liu et al, 2016] showed that as much as 30% of dipolarizations from the magnetotail can penetrate inside geosynchronous orbit.…”
Section: 1002/2016ja023304mentioning
confidence: 99%